Mosaic two : (McGraw-Hill, 1996)
Mosaic Two: A Content-Based Writing Book, 3/e, takes students step-by-step through the writing process and trains them to: * generate and develop ideas * learn language directly related to the topic * apply the appropriate rhetorical patterns to a specific writing task * evaluate and revise initial drafts of their work This book is ideal for high-intermediate to low-advanced students.